2014
DOI: 10.1186/s13054-014-0477-1
|View full text |Cite
|
Sign up to set email alerts
|

Sleep-disordered breathing is a risk factor for delirium after cardiac surgery: a prospective cohort study

Abstract: IntroductionDelirium is a frequent complication after cardiac surgery. Although various risk factors for postoperative delirium have been identified, the relationship between nocturnal breathing disorders and delirium has not yet been elucidated. This study evaluated the relationship between sleep-disordered breathing (SDB) and postoperative delirium in cardiac surgery patients without a previous diagnosis of obstructive sleep apnea.MethodsIn this prospective cohort study, 92 patients undergoing elective cardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
93
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(103 citation statements)
references
References 51 publications
6
93
1
1
Order By: Relevance
“…Other clinically important factors identified in prospective studies were depression [28,29], preoperative pain [29], and the complex of sleep disordered breathing, including, among others, snoring, obstructive sleep apnea syndrome, and the upper airway resistance syndrome [30]. ApoE4, a marker of Alzheimer's disease, was no risk factor in surgical patients [31,32].…”
Section: Psychomotoric Subtypes Of Deliriummentioning
confidence: 98%
“…Other clinically important factors identified in prospective studies were depression [28,29], preoperative pain [29], and the complex of sleep disordered breathing, including, among others, snoring, obstructive sleep apnea syndrome, and the upper airway resistance syndrome [30]. ApoE4, a marker of Alzheimer's disease, was no risk factor in surgical patients [31,32].…”
Section: Psychomotoric Subtypes Of Deliriummentioning
confidence: 98%
“…Portable sleep monitoring is relatively inexpensive and convenient but the lack of technical oversight during the study can lead to inadequate data, as was found in 19% of the recordings in this study where insufficient data resulted in the exclusion of 22 patients [1]. In addition, the inability of portable systems to monitor sleep often leads to an underestimation of the true AHI, which could affect the nature of the relationship between sleep apnea and postoperative delirium.…”
Section: Main Textmentioning
confidence: 88%
“…In this edition of Critical Care, Roggenbach and colleagues provide additional support to an association between obstructive sleep apnea (OSA) and postoperative delirium [1]. OSA has been linked to poor cardiovascular and neurologic outcomes, including cognitive dysfunction, in the outpatient setting [2,3].…”
Section: Main Textmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, two prospective studies utilizing PSG-or HSAT-confirmed diagnoses of OSA and a standardized definition of postoperative delirium have found significant correlations between OSA and the incidence of delirium after surgery [116,117]. One investigation found the rate of delirium after orthopedic surgery to be increased 2.5 fold if OSA was present [117], while the other noted a sixfold increase in delirium following cardiac surgery in patients with an AHI ≥ 19 [116]. Neither study noted a correlation with hypoxemia and incidence of delirium.…”
Section: Neurologic Complicationsmentioning
confidence: 99%